Use of dried carrot pomace in the technology of wheat bread for elderly people - Hryshchenko, Anna; Bilyk, Olena; Bondarenko, Yuliia; Kovbasa, Vladimir; Drobot, Vira (My University, 2019)
The paper considers the technological properties of dried carrot pomace obtained in the technology of organic direct pressing juices. Its use as a valuable source of food fibre and β-carotene in bread technology for elderly people has been substantiated. It has been established that dried carrot pomace has a larger particle size than flour, and its water absorption capacity is higher by 65%. A 5–15% dose of pomace makes the formation of dough longer by 1.5–6.5 min, significantly increases its viscosity and stability, as well as acidity. Due to the content of sugars available for yeast fermentation, the pomace contributes to the intensification of gas formation. The amount of wet gluten in pomace-containing dough decreases, as well as its water absorption capacity, and its resilience increases. This affects the structural and mechanical properties of dough, which has a decisive effect on the porous structure of finished products and their specific volume. A high quality of bread is achieved when the dose of dried carrot pomace is up to 5%, which helps to improve the colour and the taste. With an increasing dose, the specific volume and porosity of the products decrease. It has been proved that, due to the content of pectin and high hydrophilic properties, carrot pomace slows down the process of staling of bakery products. Calculations have shown that with the addition of 5% of the pomace, the content of β-carotene in 100 g of bread increases by 15 times, and the fibre content by 3.4 times. With the consumption of 277 g of such bread, elderly people’s daily requirement of β-carotene is satisfied by 100.8%, and the that of dietary fibre by 4.1%.
Keywords: dried carrot pomace; β-carotene; special-purpose bread; elderly people; сушені морквяні вичавки; β-каротин; люди похилого віку; хліб спеціального призначення; кафедра технології хлібопекарських і кондитерських виробів